Impact of soil compaction on common bean yield in East Africa - Jha, Prakash K.; Beebe, Stephen E.; Urban, Milan Oldřich; Preciado Gutiérrez, Camilo A.; Ramírez Villegas, Julián Armando (2022)
Bean yield can decrease up to 73% in the East Africa region (EAF, consisting of Ethiopia, Tanzania and Uganda) under soil compaction (with an increase in bulk density of up to 17%) combined with drought stress, althoughimpact of soil compaction alone on bean yield is relatively less – around 12%. Therefore, the target of increasing bean yield (set, for example, by the CGIAR Excellence in Breeding Platform) to meet the dietary requirements of the global population cannot be realized without properly understanding the extent of the problem caused by compaction combined with drought stress. This brief is based on the findings from Jha et al. (under preparation).